Electron induced fragmentation of sulphur containing biological prototypes: Thiaproline and taurine - Lange, Emily (2018)
Here we present negative ion formation driven by electron transfer in atom (potassium) molecule collision and dissociative electron attachment in sulphur containing compounds, probing the influence of sulphur atoms in the decomposition mechanism of two biological relevant molecules: thiaproline and taurine.